Propuesta de un Sistema de Gestión Ambiental basado en la norma ISO 14001:2015 para la planta procesadora “Sierralac” parroquia Cajabamba - Catucuago Cuatucuago, Katy Ibeth (2022)
The processing plant "Sierralac" is one of the most important sectors within the food chain, whose main economic activity is the production of fresh cheese and soft cheese, during the process of elaboration, a considerable risk to the environment is generated. For this reason, a System of Environmental Management based on the NTC-ISO 14001:2015 is stated, which includes a better control and management in its processes; Therefore, an initial environmental diagnosis was developed in order to determine the internal and external characteristics of the micro- business, subsequently, the identification of environmental aspects and the evaluation of environmental impacts were carried out using the modified Leopold and Vicente Conesa Fernández matrices, resulting in the main effects on the environment such as the generation of liquid effluents, solid waste, water, and energy consumption. Taking this information into account, a checklist was applied, determining that the microenterprise only complied with 3% of the NTC-ISO 14001: 2015 requirements, demonstrating the lack of an Environmental Management System, for which an Environmental Management Manual consisting of a policy, objectives, goals, programs, procedures and environmental records. If this proposal is implemented, compliance with 72% of the standard is expected, guaranteeing a continuous improvement in the environmental performance of its processes and thus contributing to sustainable development in its three axes (environmental, social, and economic) to obtain greater competitiveness in the market